Effects of Environmental Conditions on Photovoltaic Generation System Performance with Polycrystalline Panels (2021)
Photovoltaic solar energy is the third most widely used renewable source worldwide, after hydroelectric and wind energy, and this energy source requires experimental and theoretical development in specific topics such as the effect of environmental conditions on energy performance. Thus, this study's main objective was to determine the influence that meteorological conditions have on the performance of solar photovoltaic systems, based on measurements from a measurement station installed in the city of Barranquilla-Colombia, to determine the factors that significantly affect the system’s energy efficiency deviation. The experimental results show a dependence of the solar panel energy performance on some weather conditions, which is an uncontrolled phenomenon such as the ambient temperature and the atmosphere's humidity. Also, solar panel temperature and irradiance were the parameters with greater importance in the systems power generation. Also, the panel temperature must be controlled to obtain the desired response, because the panel temperature is inversely proportional to the voltage and directly proportional to the current. However, the negative effect of increased panel temperature in sunny climates is compensated by increased solar hours, so the summer system has less instantaneous efficiency, but it has higher solar output throughout the day. Therefore, solar energy production study should be related to total daily production.